Empowering Bedside Nurses to Lead Discussion Groups. Issue 1 (January 2018) - Anspach, Kelli M.; Bruce, Laura; Rutberg, Shannon
Abstract : This article focuses on an approach three clinical nurse educators used to empower their Telemetry Education Nurse Team to grow professionally. The clinical nurse educators mentored the Telemetry Education Nurse Team, who were then able to facilitate successful discussion groups for their organization.